Intercultural Communication Strategies for the Implementation of the Law of Victims with Indigenous Communities: The Case of the Emberá Katío Choromandó Community in Dabeiba (Antioquia) (2018)
According to the Law of Victims in Colombia (Law 1448 of 2011, and its Regulatory Decree 4633 of the same year), an indigenous community like the Emberá Katío Choromandó of Dabeiba (Antioquia) meets the conditions to be considered as affected by the actors of the armed conflict and, therefore, to be a subject of rights. However, this law remains budding when it aims to offer elements of interculturality that allow its effective appropriation. Faced with this, an accompaniment is proposed to the community of Choromandó in the co-creation of a peace proposal, adapting the Victims' Law to their needs within the framework of agreements with the Revolutionary Armed Forces of Colombia (FARC) in Havana (Cuba). Through a participatory design, in accordance with the conceptual and methodological assumptions both of the research-action-participation of Orlando Fals Borda, and of intercultural communication of Edward Hall, a series of demands that start from the understanding of the Embera worldview is established, which underlies its indissoluble space-time dimension, until the validation of its autonomy, which translates into the preservation of its identity, stemmed from the filiation to the territory. The aspects of interculturality that were significant in the process included the following: Non-verbal communication and paralanguage, the diverse value of space and time (polytopia and polychrome) to understand the interrelations of the settlers (proxemia), and the joint work with the mestizo population to replace the lack of knowledge of the native language, and to enter into the communication practices of a culture without a written language.